The Role of Strategic Approaches in the Planning and Development of Educational Institutions - Baidowi, Ahmad; Ratna Dewi, Erni (Al-Ilmu, 2025)
In the era of globalization and digital transformation, educational institutions face complex challenges in maintaining performance, aligning strategies with stakeholder expectations, and adapting to external uncertainties. This study aimed to examine the effectiveness of a participatory and adaptive strategic planning model in enhancing institutional performance. A mixed-methods case study design was employed, combining qualitative interviews and focus group discussions with quantitative surveys of diverse stakeholders, including school leaders, teachers, students, and parents. Data analysis involved thematic coding of qualitative findings and regression analysis of survey responses. The results revealed that embedding a five-phase framework visioning, stakeholder orientation, situational analysis, strategic formulation, and adaptive monitoring significantly strengthened institutional outcomes. Stakeholder engagement through inclusive consultations improved trust, ownership, and collaborative commitment. Adaptive monitoring mechanisms facilitated responsiveness to shifting priorities, while the integration of learning analytics supported evidence-based decision-making. Furthermore, participatory approaches cultivated systems thinking and cultural alignment across departments, reinforcing long-term strategic orientation. In resource-constrained contexts, participatory planning enabled creative resource mobilization and increased student involvement in institutional priorities. In conclusion, the findings confirm that participatory and adaptive strategic planning enhances planning quality, strengthens stakeholder participation, and improves institutional resilience. The study contributes theoretical insights into adaptive planning cycles and provides practical guidance for sustainable educational development.